2013
DOI: 10.1017/jfm.2013.64
|View full text |Cite
|
Sign up to set email alerts
|

Variable density and viscosity, miscible displacements in horizontal Hele-Shaw cells. Part 2. Nonlinear simulations

Abstract: Direct numerical simulations of the variable density and viscosity Navier–Stokes equations are employed, in order to explore three-dimensional effects within miscible displacements in horizontal Hele-Shaw cells. These simulations identify a number of mechanisms concerning the interaction of viscous fingering with a spanwise Rayleigh–Taylor instability. The dominant wavelength of the Rayleigh–Taylor instability along the upper, gravitationally unstable side of the interface generally is shorter than that of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Results of experiments in rectilinear displacements could also be easier to compare with theoretical stability analyses or full numerical solutions of the relevant equations. 6,7 Simulations could moreover test the influence of the different parameters of the problem on the evolution of the pattern in 3D. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of experiments in rectilinear displacements could also be easier to compare with theoretical stability analyses or full numerical solutions of the relevant equations. 6,7 Simulations could moreover test the influence of the different parameters of the problem on the evolution of the pattern in 3D. …”
Section: Discussionmentioning
confidence: 99%
“…1 In horizontal systems, the density jump is in the direction perpendicular to gravity and the stability of the interface is classically considered to depend only on the viscosity difference: viscous fingering can be observed when the less viscous fluid is injected into the more viscous one while the reverse displacement is viscously stable. The influence of density differences across the miscible interface on the viscous fingering pattern has been recently addressed by both linear stability analysis 6 and nonlinear simulations 7 of the full 3D Stokes problem. It has been shown that a buoyancy-driven instability can act within the gap of the cell on the upper side of the finger.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 8) (John et al 2013). The density difference between the displacing and displaced fluids gives rise to an additional dimensionless parameter F defined as…”
Section: Resultsmentioning
confidence: 98%
“…These stripes result from streamwise, counter-rotating vortices, such as can be seen in Figs. 10 and 20 in John et al (2013). Talon et al (2013) conducted a detailed linear stability analysis of this density-driven instability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation